An Investigation On Pre-Service Elementary School Teachers’ Mathematics Anxiety - Rahayu, Lina Puspitaning; Mustadi, Ali; Sarjiman, Petrus (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
The aims of this study are to (1) determine the level of mathematics anxiety (MA) of pre-service elementary school teachers, (2) compare the MA among pre-service elementary school teachers in terms of gender, and (3) compare the MA among pre-service elementary school teachers in terms of the semester. This research employed a quantitative approach with comparative research design. In addition, the samples were 498 pre-service elementary school teachers. The instrument used is the Revised-Mathematics Anxiety Survey (R-MANX) developed by Bursal and Paznokas (2006). R-MANX consists of 30 statement of a 5-point Likert scale. The data analysis was processed using one-way ANOVA assisted by SPSS version 23. The findings reveal that the MA of pre-service elementary school teachers is high. Further, it is revealed that there is no significant MA difference between male and female pre-service elementary school teachers. Also, there is no significance of MA difference among pre-service elementary school teachers who are in 2nd semester, 4th semester, and 6th semester. Therefore, the results of this research imply that MA can affect pedagogical competence of a teacher and it could have an impact on the way the teacher manages the class.